Harvest Stages and Umbel Order Contribution on Eryngo (Eryngium foetidum L.) Seed Yield and Quality - Boonsong Ekpong; Sutevee Sukprakarn (Agriculture and Natural Resources, 2006)
Harvest stages and umbel order contribution were studied from October 2003 to August 2004 to determine the optimum harvest time for eryngo seed production. Maximum seed yield of eryngo accession EF007 was obtained from the seventh (H7) and the eighth (H8) harvest stages with an average of 16.5 gm/m2 when seed color was brownish black with 90% germination. The greatest contribution to seed yield was mainly from the seventh umbel order.